PENINGKATAN NETRALITAS PEJABAT BIROKRASI ASN (APARATUR SIPIL NEGARA) DI KABUPATEN MAGELANG - Yuwono, Endro; Syaflan, Meidi (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2024)
This study aims to see officials in Magelang Regency carry out Bureaucratic Neutrality Improvement by using qualitative research types. Research is carried out on community leaders, DPRD members, ASN, and officials in the Magelang Regency government environment. This study resulted in several findings why ASN is not neutral and does not comply with existing laws or regulations, several violations and efforts to increase ASN Neutrality so that this research can be a reference, useful and beneficial for future researchers and for the Magelang Regency government. From some of these findings it can be concluded that political officials who are elected in the elections directly become regional heads of regents and deputy regents, there has been a fundamental and phenomenal change in the regional government system in Indonesia which is marked by the rolling of the regional head election mechanism (Pilkada). direct since 2005. This direct election is a mandate from reform. The public's demand to carry out direct elections is due to the fact that the election of regional heads through representatives was previously considered undemocratic because only dozens of DPRD members were elected. Actually the election of a regional head in a direct election will get influential leadership because it is elected by the people directly, only this is not as expected because what happens is that the elected regional head or regent in Magelang Regency is carried by Paruai which is expected because what happened was elected being a regional head or regent in Magelang Regency is carried out by a political party so that the tendency to be neutral is felt to be lacking because with his power as the regent's supervisory officer, he has the power to choose, appoint and dismiss bureaucratic officials who are disloyal and oppose the policies that have been declared by the regent.